Depressive hypertension: A proposed human endotype of brain/gut microbiome dysbiosis - Stevens, Bruce R.; Pepine, Carl J.; Richards, Elaine M.; Kim, Seungbum; Raizada, Mohan K. (The American heart journal, 2021)
Hypertension (HTN) is frequently linked with depression (DEP) in adults with cardiovascular disease (CVD), yet the underlying mechanism and successful management remain elusive. We approached this knowledge gap through the lens that humans are eukaryote-prokaryote "meta-organisms," such that cardiovascular disease dysregulation is a mosaic disorder involving dysbiosis of the gut. We hypothesized that patients diagnosed with hypertension plus depression harbor a unique gut microbial ecology with attending functional genomics engaged with their hosts' gut/brain axis physiology. Stool microbiome DNA was analyzed by whole metagenome shotgun sequencing in 54 subjects parsed into cohorts diagnosed with HTN only (N = 18), DEP only (N = 7), DEP plus HTN (DEP-HTN) (N = 8), or reference subjects with neither HTN nor DEP (N = 21). A novel battery of machine-learning multivariate analyses of de-noised data yielded effect sizes and permutational covariance-based dissimilarities that significantly differentiated the cohorts (false discovery rate (FDR)-adjusted P ≤ .05); data clustering within 95% confidence interval). Metagenomic significant differences extricated the four cohorts. Data of the cohort exhibiting DEP-HTN were germane to the interplay of central control of blood pressure concomitant with the neuropathology of depressive disorders. DEP-HTN gut bacterial community ecology was defined by co-occurrence of Eubacterium siraeum, Alistipes obesi, Holdemania filiformis, and Lachnospiraceae bacterium 1.1.57FAA with Streptococcus salivariu. The corresponding microbial functional genomics of DEP-HTN engaged pathways degrading GABA and beneficial short chain fatty acids (SCFA), and are associated with enhanced sodium absorption and inflammasome induction. These data suggest a new putative endotype of hypertension, which we denote “depressive-hypertension” (DEP-HTN), for which we posit a model that is distinctive from either HTN alone or DEP alone. An "endotype" is a subtype of a heterogeneous pathophysiological mechanism. The DEP-HTN model incorporates a unique signature of microbial taxa and functional genomics with crosstalk that putatively intertwines host pathophysiology involving the gastrointestinal tract with disruptions in central control of blood pressure and mood. The DEP-HTN endotype model engages cardiology with gastroenterology and psychiatry, providing a proof-of-concept foundation to explore future treatments, diagnosis, and prevention of HTN-coupled mood disorders.